1984
DOI: 10.1093/ajcn/39.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Effect of consuming fiber from corn bran, soy hulls, or apple powder on glucose tolerance and plasma lipids in type II diabetes

Abstract: The effects of consuming corn bran, soy hulls, or apple powder on glucose and lipid metabolism were investigated in two studies of persons with type II diabetes. Fiber sources, completely or partially added to bread, were incorporated into subjects' self-selected diets. Low fiber white bread served as a control. In study A, 10 subjects consumed 26 g fiber source daily; in study B, eight subjects consumed 52 g fiber source. Biochemical tests, including a 2-h postprandial glucose test using a low fiber formula m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(32 citation statements)
references
References 24 publications
1
30
0
1
Order By: Relevance
“…Animal studies have demonstrated that soy protein and soy isoflavones improve glycemic control, lower insulin requirement, and increase insulin sensitivity (Vahouny et al, 1985;Iritani et al, 1997;Wagner et al, 1997;Lavigne et al, 2000). Similar benefits have also been documented in several intervention studies with soy supplements (soy protein, soy fiber, and soy isoflavones), but results have been inconsistent (Mahalko et al, 1984;Lo et al, 1986;Hermansen et al, 2001;Jayagopal et al, 2002). One cross-sectional study has examined the effect of usual dietary intake of isoflavones on glucose metabolism and observed an inverse association with insulin level (Goodman-Gruen & Kritz-Silverstein, 2001).…”
Section: Introductionmentioning
confidence: 72%
“…Animal studies have demonstrated that soy protein and soy isoflavones improve glycemic control, lower insulin requirement, and increase insulin sensitivity (Vahouny et al, 1985;Iritani et al, 1997;Wagner et al, 1997;Lavigne et al, 2000). Similar benefits have also been documented in several intervention studies with soy supplements (soy protein, soy fiber, and soy isoflavones), but results have been inconsistent (Mahalko et al, 1984;Lo et al, 1986;Hermansen et al, 2001;Jayagopal et al, 2002). One cross-sectional study has examined the effect of usual dietary intake of isoflavones on glucose metabolism and observed an inverse association with insulin level (Goodman-Gruen & Kritz-Silverstein, 2001).…”
Section: Introductionmentioning
confidence: 72%
“…A very modest improvement in blood glucose attributed to fiber intake from soy beans has been reported in type 2 diabetic subjects both in some acute (17) and some more long-term experiments (36), while this was not seen in other studies (37). No change in insulin levels occurred (17,38).…”
Section: Glucose and Insulin Responsesmentioning
confidence: 89%
“…Many studies in animals as well as in humans suggest that soy has beneficial effects on diabetes mellitus, and several studies in obese humans and animals suggest that soy as a source of dietary protein has significant antiobesity effects (Table 2) [103][104][105][106][107][108][109][110][111][112][113][114][115][116][117]. Mahalko et al fed different sources of fiber to type 2 diabetic subjects for 2 to 4 weeks and observed beneficial effects of soy hulls on glucose tolerance, lipid indexes, and glycated hemoglobin [110].…”
Section: Phytoestrogens and Glucose Metabolism And Obesitymentioning
confidence: 99%
“…Mahalko et al fed different sources of fiber to type 2 diabetic subjects for 2 to 4 weeks and observed beneficial effects of soy hulls on glucose tolerance, lipid indexes, and glycated hemoglobin [110]. Tsai et al observed that in obese subjects with type 2 diabetes, soy polysaccharides significantly reduced increases in postprandial serum glucose and triacylglycerol concentrations [108].…”
Section: Phytoestrogens and Glucose Metabolism And Obesitymentioning
confidence: 99%